Implementation of Rooftop Solar Photovoltaic Systems in Educational Facilities at Ibu Kota Nusantara (IKN) - Buruhan Haji Shame; Mohammed M. Haji; Singgih Dwi Prasetyo (Mekanika: Majalah Ilmiah Mekanika, 2025)
The primary objective of this research is to evaluate the feasibility and potential benefits of integrating solar Photovoltaic (PV) systems in educational institutions within the new capital. The Hybrid Optimization of Multiple Energy Resources (HOMER) energy modeling software was utilized to achieve this, enabling a detailed analysis of the project's viability for investment over a specified timeframe. Key metrics such as Net Present Cost (NPC), Cost of Energy (COE), and Break-Even Point (BEP) were emphasized to assess the economic implications of the project. The findings of the research reveal that the rooftop solar PV system for schools in Ibu Kota Nusantara (IKN) has NPC of IDR 15,865,110,000.00, COE of IDR 1,174.26 per kWh, and a BEP occurring in the sixteenth year, as indicated by the simulation results. These outcomes suggest that the rooftop solar PV project is not only a viable solution but also holds significant potential for development. Furthermore, it supports the overarching goals of the capital relocation program while promoting the adoption of renewable energy sources in Indonesia, thereby contributing to a more sustainable future for the nation.